A STUDY ON CODE SWITCHING USED BY MALINAU STUDENTS IN LAMONGAN - Ningsih, Senja Sri Wanti; Luthfiyati, Dian (E-Link Journal, 2020)
Language is foremost a means of communication used by people to convey their ideas and feelings to others when they talk directly or indirectly. Current phenomenon is common in society the code switching used by individuals who live in a bilingual or multilingual community in which the code switching can occur. The researcher chooses one of Malinau students in Lamongan. Her name is "Siti Bakhiatus Sholikhah" Faculty of Fisheries, Lamongan Islamic University, on eighth semester.The purpose of this study is to find out the types of code switching and find out the functions of code switching used by Malinau Student in Lamongan. This study examines the types of code switching that occurred during the conversations used by Malinau Students in Lamongan. The research design of this study is using qualitative descriptive method. The collection technique of the data is from of recording and chatting in social media : like a WhatsApp and Facebook from â€œLikaâ€™sâ€ talks. The data analysis techniques used found that are preparing, reading and undesrtanding, coding and classifying, interpreting and drawing te conclusion. From this data found the types and functions of code switching are analyzed by using the theory of Poplackâ€™s and Apple and Muysken. From the results of analysis, three types of code switching (tag switching, inter-sentential switching and intra-sentential switching) and four functions of code switching are (referential function of code switching, directive function of code switching, expressive function of code switching and metalinguistic function of code switching).Â